Causal Analysis of the Pinion Teeth Failure in a Limestone Reclaimer (2020)
This paper presents a causal analysis of an unexpected failure of the pinion teeth of a large reducer installed in a limestone reclaimer which is part of a raw material transportation system of a cement factory. The Montano methodology is applied. It includes a collection of documentation, evidences, evaluation of failure mechanism by visual inspection and some hypothesis and their validation based on the analysis of the material resistance. It is demonstrated that although the teeth of the pinion were made of a suitable material and cemented correctly, they worked overloaded due to the presence of large rocks in the raw material. A resulting increase of contact tensions in the teeth over the allowed limits led to a fatigue failure process which is described in this work. The results of the analysis can be of great interest in order to develop preventive measures and avoid future undesired plant stoppages and economic losses.